P（2-RPS）&U Reconfigurable Rehabilitation Mechanism Used for Human Joint and Its Kinematics Analysis - Wangwang Guo; Ruiqin Li; Fengping Ning (Jixie chuandong)
Based on the motion mechanism of human joints and reconfigurable concept， a P（2-RPS）&U reconfigurable rehabilitation mechanism is proposed. By locking the kinematic pairs to change the movement mode of the moving platform， the rehabilitation training of human elbow joint， knee joint and ankle joint can be realized， respectively. The inverse solution of the P（2-RPS）&U reconfigurable rehabilitation mechanism is analyzed and its position singularity is analyzed based on the screw theory. And the two singularity positions of the mechanism are obtained. The singularity positions can be avoided by adding the driver. The kinematics simulation of the P（2-RPS）&U reconfigurable rehabilitation mechanism is carried out by using Adams software. The simulation results show that the mechanism could reach the range of rehabilitation movements of human elbow， knee and ankle joints， and satisfy the rehabilitation requirements of damaged joints.